Pelatihan Manajemen Keuangan UMKM Kecamatan Kaliwungu - Ninik Dwi Atmini; Rita Andini; Utami Puji Lestari; Ahmad Dwi Nurdiyanto; Ika Susanti (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
Micro, Small, and Medium Enterprises (MSMEs) in Kaliwungu District often face financial management challenges, including limited knowledge in basic bookkeeping and financial statement preparation. This study aims to enhance the financial literacy and management skills of MSME actors in Kaliwungu District through comprehensive training. The method involved three stages: preparation (licensing, media, and material preparation), implementation (lectures, tutorials, and discussions), and evaluation. The training, held on May 15, 2024, was attended by 43 MSME participants from Forkom UMKM Kaliwungu. The results showed a significant increase in participants' knowledge and understanding of financial statements, evidenced by active participation in discussions and practical exercises. Post-training evaluation indicated that 53% of participants understood the material well, and 33% understood it very well. The training methods were also positively received (45% strongly agreed, 40% agreed). This program successfully empowered MSME actors to prepare financial reports, contributing to better financial management and supporting the sustainable economic development of MSMEs in Kaliwungu.